Pharmacogenetics of anti-seizure medications in Arab countries: a comprehensive review - Rania Magadmi (Future Science OA, 2025)
Epilepsy, a prevalent neurological disorder, is characterized by recurring seizures due to atypical neural activity, impacting millions globally. Epileptic seizures are the sudden, involuntary jerking or trembling movements caused by abnormal neural activity and may lead to damage in the brain or other parts of the body. Although epilepsy is usually manageable with anti-seizure medications (ASMs), a considerable subset of patients experiences drug resistance or suboptimal treatment responses, highlighting the need for a more elaborate approach to therapy. Studies show that genetic factors significantly influence not only the susceptibility to epilepsy but also the variability in individual responses to ASMs. This signifies the importance of personalized medicine in optimizing treatment guidelines based on genetic profiles. This review examines the pharmacogenetic factors influencing the efficacy and safety of anti-ASMs in Arab populations. In populations across Saudi Arabia, Jordan, Egypt, Tunisia, and Iraq, genetic testing for variants in genes like MTHFR, MDR1, ABCB1, miR-146a, GABARG2, IL-1β, EPHX1, and CYP3A422 can predict drug resistance, and response, improve drug dosing, and minimize ADRs. Clinicians can personalize therapy by employing specific genetic markers associated with drug metabolism and efficacy, leading to better treatment outcomes and reduced risk of drug-induced complications.